Expansão residencial e o aumento de inquilinato no centro da cidade de Lomas de Zamora, Buenos Aires. Argentina. - Bárbara Teresa Romano (Confins)
The cities in the metropolitan region of Buenos Aires have been the target of an important increase in real estate activity in the period after the 2001 crisis. However, the increase in the residential offer has not translated into possibilities of access to own housing, as the number of tenants has increased. In this work, the objective is to analyze the rental process in the city of Lomas de Zamora, with the increase in the number of buildings and the expansion of commercial stores that determined the configuration of an area dubbed by the real estate companies as “Las Lomitas”. In this sense, the research aims to analyze the interference of State policies and also of the market as agents that promote lease in the center of Lomas de Zamora.